Política externa brasileira no setor energético sul-americano entre 2003 e 2010 - Colnago, Renan de Campos [UNESP] (2020)
Energy began to play a central role in international relations and foreign policy since the 1970s. In South America, issues related to this topic were the subject of discussions and reforms at the state level, especially since the 1990s, with the special attention of the governments. In Brazil's foreign policy, the energy agenda has played a central role since the 2000s. With the rise of regional integration processes, energy has played a prominent role in Brazil's relationship with its South American neighbors. In this sense, analizes of Lula’s foreign policy proliferate, ranging from the most traditional to the most unorthodox in the field of International Relations. The focus of this work is analize the brazilian foreign policy in the energy sector on South America between 2003 and 2010. It is argued, then, that the foreign policy of that period provided physical interconnection in the energy field between the countries of the region, but was unable to enable to create a broad and effective process of energy integration, based on the preferences of the bloc in power that made up the political plataform of suport of the Lula’s government.